Enzymes and genes involved in aerobic alkane degradation - Shao, Zongze; Wang, Wanpeng (Frontiers in Microbiology, 2013)
Alkanes are major constituents of crude oil. They are also present at low concentrations in diverse non-contaminated because many living organisms produce them as chemo-attractants or as protecting agents against water loss. Alkane degradation is a widespread phenomenon in nature. The numerous microorganisms, both prokaryotic and eukaryotic, capable of utilizing alkanes as a carbon and energy source, have been isolated and characterized. This review summarizes the current knowledge of how bacteria metabolize alkanes aerobically, with a particular emphasis on the oxidation of long-chain alkanes, including factors that are responsible for chemotaxis to alkanes , transport across cell membrane of alkanes , the regulation of alkane degradation gene and initial oxidation.